Variation in guanosine 5' ,3'-tetraphosphate levels in Chromatium. - Klaussmann, G (1977)
Chromatium produces guanosine 5' ,3'-tetraphosphate, but there appears to be no correlation between guanosine 5' ,3'-tetraphosphate concentration and the inability of the organism to grow in certain light-dark regimes.